Theoretical approximation on human needs and their relation with housing configuration, imaginary and the city - Garcia, Luz Marcela (UNIVERSIDAD DE SONORA, 2021)
Current urban and housing configurations and social imaginary conception condition fulfillment of essential human needs; given dominant mercantilist ideology that subjugates man towards scenarios that resemble Procustes myth, in order to impose unhealthy spaces for the sake of uniformity. In this article, the methodological framework includes deductive and descriptive conceptual analysis, information on housing, social imaginaries and urban phenomena; additionally, it is an approximation of interdisciplinary character. Descriptive focus will allow binding of human needs per Maslow's theory with direct and indirect implications on man’s wellbeing; furthermore, in order to establish a common thread throughout, resources from the narrative method are implemented. The article’s objective is to carry out an analysis between human needs and contemporary urban configuration, housing conditions and their character and influences into the social imaginary as to find possible bonds to human wellbeing within them.